A Bakhtinian Dialogical Approach to Understanding Young Vietnamese Children’s Narratives and Identities Formation in Preschools (Journal of Contemporary Educational Policies and Practices, 2022)
Previous studies have claimed that young children’s everyday narratives reflect their identities formation. Guided by Bakhtinian theory of dialogism and qualitative research, this paper aims to explore two young Vietnamese children’s everyday narratives and identities formation in a preschool in Hanoi. Young children’s identities formation is understood as an ongoing process of their articulation of others’ words to make sense of themselves and the world. Children’s narratives are conceptualized in multimodal forms of language (e.g. verbality, gestures, body movements) and were collected through diverse resources (e.g. close observation, informal conversations, fieldnotes, and artifacts). Semistructured interviews and informal conversations were conducted to access parents’ and teachers’ narratives about children. Data analysis was completed through two steps (including transcription and analysis of children’s stories). The findings showed that children are agentive narrators in telling and constructing themselves. Cultural resources and adults’ beliefs and practices are contextual factors influencing children’s identities. These findings both support and differ from prior studies on teacher-child interactions in the Vietnamese context and recommend preschool teachers to design their classes as the dialogical environment to support children’s well-being.